Greenhouse gas and techno-economic evaluation of transportation fuels from Integrated Hydropyrolysis and Hydroconversion (IH2) - Subramaniam, Gopi (My University, 2021)
The aim of this thesis was to evaluate the production of gasoline and diesel using woody biomass feedstock via the Integrated Hydropyrolysis and Hydroconversion (IH2) technology from a technical, economic and greenhouse gas (GHG) emissions perspective. The methodology was first to model the IH2 process based on published experimental data via a combination of mass and energy balances and Aspen Plus computer simulation. The results indicated a liquid hydrocarbon yield of 26% on a dry ash free feed basis and an overall system efficiency of 60%. The results from the process modelling were then used to build up an operating expenditure (OPEX) estimate for an IH2 plant based on two future energy market price scenarios, which then allowed for an estimation of the capital expenditure that could be supported while maintaining a reasonable operating margin. The results showed that OPEX was primarily driven by the biomass feed price, and to a much lesser extent the price of wholesale grid electricity and external refinery final processing costs. Furthermore, the capital expenditure that could be supported was shown to be high compared to previously published capital cost estimates for the IH2 process. This result was shown in scenarios both with and without a supportive policy environment for biofuels. Finally, a well-to-wheel GHG emissions balance was estimated. The relative emissions savings compared to the corresponding fossil transportation fuels were primarily dependent on the assumed marginal user of biomass and if the biomass was considered a limited resource. If biomass is a limited resource and the marginal user a coal fired power plant, the emissions savings were approximately 38%, while the savings were greater than 97% if biomass was not considered a limited resource.